THE EFFECTIVENESS OF SONGS FOR TEACHING SPEAKING - Wijaya, Titis Wisnu (Journal of Foreign Language Teaching and Learning, 2018)
The primary motive for comprehending language is to create a communication. Speaking becomes a difficult thing to do for Indonesian learner when the learner wants to increase the speaking ability to the learner. Most learners are good in theory, yet bad in practice. Whereas speaking is the purpose of learning English. In this case, innovation in speaking skill must be innovative. Teaching speaking ability is not only delivering the material but also giving something different way to make learner interested. The research subject was the fourth-semester students in the academic year of 2013/2014. The students would be in two classes, i.e., the experimental and control group. The classes started with pre-test. The post-test fourth-semester in the last meeting after treatment. The researcher obtained the data from a speaking test and continued to analyze by inferential analysis. The research findings showed that the research had a gap in the students? speaking ability in the experimental group and the control group. From the data analysis, the scores in experimental and the control group increased.Moreover, the increase in the experimental group was better than the control group. In the experimental group has three categories, i.e., good (2 students), fair (18 students), and poor (1 student). Post-test mean (17.47) was higher than the pre-test (10.19). The control group had three different categories, i.e., fair (5 students), poor (12 students), and very poor (3 students). Post-test mean (13.85) was higher than the pre-test (10.05). The data showed that post-test mean in the experimental group (17.47) was higher than the post-test mean in the control group (13.85). Therefore, the hypothesis ?It has a high score in learning to speak using a song for students in the experimental group? was accepted.